Perfil sensorial, aceitação e caracterização em compostos bioativos de néctares mistos de frutas tropicais - Fonseca, Ana Valquiria Vasconcelos da (2014)
The composite beverages with more than one fruit is a tendency of both national and international market, offering advantages such as nutrient supplementation of different fruits, allowing increased nutritional characteristics and development of new flavors. Despite its great expression, are still few studies involving the removal of the sensory attributes describing the quality of juices and nectars mixed tropical fruits. Therefore, the aim of this work was to study the sensory profile of mixed tropical fruit nectars, and to evaluate their chemical, physicochemical, rheological and sensory acceptance characteristics. For this, pasteurized and frozen pulps tropical fruit were used such as of pineapple, acerola, caja, cashew apple, guava and mango provided by producer in Ceará, water for dilution and sucrose, being formulated mixed nectars from these six pulps of tropical fruits, totaling 15 different formulations. All mixed nectars were processed with a content of 35% pulp, being composed of two distinct pulps used in the same proportion, with a fixed amount of soluble solids of 11 °Brix. The pulps and mixed nectars were evaluated for their chemical and physico- chemical characteristics of pH, total soluble solids (°Brix), total acidity, total and reducing sugars, vitamin C, total carotenoids, total anthocyanins, total flavonoids, total extractable polyphenols, color parameters and total antioxidant activity. From fifteen formulations obtained, sensory acceptance tests with randomized complete block for further study of the sensory profile of those most well accepted were performed. Nectars with a mean equal to or greater than 7.0 in acceptance testing were evaluated by Quantitative Descriptive Analysis (QDA® ). For this analysis, the tasters were initially recruited by questionnaires and pre - selected by triangular tests and Wald sequential analysis. The survey of descriptive terms was performed by assessors gathered in groups under the supervision of a moderator, where panelists evaluated each of the five mixed nectars formulations described all descriptive terms that characterized each sample with respect to appearance, aroma, flavor and texture attributes. Through various other sessions each descriptor has been consensually defined, along with their references and elaborated the evaluation ballot. Nine judges were selected for the final team, using as criteria the discrimination, reproducibility of results and consensus with the team. Five samples of mixed nectars of tropical fruits were evaluated in three sessions, according balanced complete blocks. Still an acceptance test with mixed nectars used in QDA® was performed for hundred untrained. It was also rated the rheological behavior of these mixed nectars of tropical fruits through a concentric cylinder rheometer. Finally, a correlation between the physicochemical, chemical, sensory and rheological data was performed. To analyze the results, were used analysis of variance (ANOVA) and Tukey's test using SAS statistical software. To visualize the sensory profile of the samples, were used the spider graph and Principal Component Analysis (PCA). According to the results, it was observed that all pulps were found in accordance with the standards required by the legislation or in accordance with other authors for the chemical, physicochemical and microbiological parameters. All mixed nectars showed chemical and physicochemical results according to the available literature, having very similar characteristics, except for those with acerola in its formulation, since they showed higher vitamin C and total antioxidant activity. The sensory profile of the samples shown through the spider graph has been well defined for each of the samples, mainly because they have the same distinct characteristics. Nectars also showed good repeatability when observing the graph of Principal Component Analysis (PCA), with small geometric figure or even unnoticeable once the reps were on the same line. Regarding the rheological behavior of the samples, good fits were obtained in both the Ostwald-de-Waelle as in Casson model, being characterized as non-Newtonian fluids with pseudoplastic characteristics. Nectars showed several positive and negative correlations between the physicochemical, chemical and sensory data.